Effects of ultralow topical estriol dose on vaginal health and quality of life in postmenopausal women who underwent surgical treatment for pelvic organ prolapse. Issue 8 (August 2017) - Caruso, Salvatore; Cianci, Stefano; Vitale, Salvatore Giovanni; Matarazzo, Maria Grazia; Amore, Francesca Flavia; Cianci, Antonio
Abstract: Objective: To evaluate the efficacy of low concentrations of vaginal estriol gel in postmenopausal women with pelvic static disorders before and after vaginal surgical treatment, assessing vaginal health, sexual function, and quality of life (QoL). Methods: Women affected by genital prolapse were enrolled. Vaginal health, QoL, and sexual function were investigated at baseline (T0), before surgery (T1), and 13 weeks after surgery (T2). At baseline, participants were randomized 1:1. Women in group A (38 women) were treated daily with vaginal gel containing 50 μg estriol for 12 weeks and women in group B (37 women) did not receive any estrogen treatment. After this period and before surgery, a first examination was carried out (T1). One week after surgical treatment, group A underwent randomization 1:1 to group A1 repeating estriol vaginal gel for 12 weeks, and group A2 discontinuing the estrogen treatment. The second follow-up examination (T2) was performed at the 13th week after surgery. Results: All aspects of vaginal health improved in group A on estriol before surgery with respect to baseline ( P < 0.001). After surgery, 17 participants of group A1, 16 of group A2, and 30 of group B completed the study. Group A1 (on estriol plus surgery) further improved with respect to the presurgery estriol treatment ( P < 0.01). Moreover, group A2 (T2) experienced a worsening of vaginal health versus intragroup presurgery estriol treatment ( P < 0.01), and versus intergroup surgical estriol treatment ( P < 0.05). QoL improved in women only after surgery, with ( P < 0.01) or without ( P < 0.05) estriol treatment. Finally, the sexual function of participants on estriol before surgery did not change. On the contrary, it improved after surgery in both participants on estriol ( P < 0.001) and without estriol ( P < 0.01). Moreover, surgical estriol participants had a better score than surgical no-estriol participants ( P < 0.05). Conclusions: Estriol vaginal gel (0.005%) administration significantly improved the vaginal health of natural postmenopausal women before and after vaginal surgery. Both sexual health and QoL also significantly improved after surgery.